The effects of apremilast on the QTc interval in healthy male volunteers: a formal, thorough QT study - Palmisano, Maria (Int J Clin Pharmacol Ther, 2016)
Objective: This study was conducted to evaluate the effect of apremilast and its major metabolites on the placebo-corrected change-from-baseline QTc interval of an electrocardiogram (ECG). Materials and methods: Healthy male subjects received each of 4 treatments in a randomized, crossover manner. In the 2 active treatment periods, apremilast 30 mg (therapeutic exposure) or 50 mg (supratherapeutic exposure) was administered twice daily for 9 doses. A placebo control was used to ensure double-blind treatment of apremilast, and an open-label, single dose of moxifloxacin 400 mg was administered as a positive control. ECGs were measured using 24-hour digital Holter monitoring. Results: The two-sided 98% confidence intervals (CIs) for ΔΔQTcI of moxifloxacin completely exceeded 5 ms 2 – 4 hours postdose. For both apremilast dose studies, the least-squares mean ΔΔQTcI was < 1 ms at all time points, and the upper limit of two-sided 90% CIs was < 10 ms. There were no QT/QTc values > 480 ms or a change from baseline > 60 ms. Exploratory evaluation of pharmacokinetic/pharmacodynamic data showed no trend between the changes in QT/QTc interval and the concentration of apremilast or its major metabolites M12 and M14. Conclusions: Apremilast did not prolong the QT interval and appears to be safe and well tolerated up to doses of 50 mg twice daily.